Rapid conversion to virtual obesity care in COVID‐19: Impact on patient care, interdisciplinary collaboration, and training - Jessica A. Lohnberg; Lianne Salcido; Susan Frayne; Naina Mahtani; Cheryl Bates; Michelle E. Hauser; Jessica Y. Breland (Wiley, 2022)
Abstract Objective The COVID‐19 pandemic presents challenges to maintaining interdisciplinary collaboration while transitioning care to telehealth environments. This paper describes how an intensive weight management clinic rapidly transitioned from in‐person only to a telehealth environment. Method As a program evaluation project, changes to clinic procedures were tracked on a weekly basis. Patients were invited to complete phone surveys after clinic appointments from 1 May 2020 to 31 July 2020. The survey included 12 items rated on a 5‐point scale ("strongly disagree" to "strongly agree"). Results Adaptations included converting team meetings and clinical training to phone/video platforms and transferring a complex patient tracking system to an interactive virtual format. Fifty‐eight patients completed phone surveys (81% response rate). All "agreed" or "strongly agreed" that they were satisfied with telehealth care; 51% "agreed" or "strongly agreed" that telephone visits were as good as in‐person visits; and 53% preferred phone appointments even after pandemic restrictions are eased. Conclusions It is feasible to rapidly transition to a telehealth clinic when supported by infrastructure and resources of a national, integrated healthcare system. Patient preferences include access to both telehealth and in‐person services. A blended telehealth/in‐person model that maintains interdisciplinary collaboration and training is necessary even after the COVID‐19 pandemic.